The effects of detraining and retraining periods on fat-mass and fat-free mass in elite male soccer players - Suarez-Arrones, L.; Lara-Lopez, P.; Maldonado, R.; Torreno, N.; De Hoyo, M.; Nakamura, F. Y.; Di Salvo, V.; Mendez-Villanueva, A. (PeerJ, 2019)
The aim of the study was to examine the effects of a detraining period (DTP) (i.e., off-season) with an individually prescribed training program, and a retraining period (RTP) (i.e., pre-season) combining soccer and flywheel-based strength training on fat-free mass (FFM) and fat-mass (FM) in 10 elite professional male soccer players. The present study used a controlled repeated-measures research design to investigate the changes in FFM and FM using dual-energy X-ray absorptiometry. Whole body %FM increased (effect size (ES) = 0.87 ± 0.46) and FFM reduced after DTP (ES = -0.30 ± 0.19), returning to values comparable to the end of the previous season after RTP. At regional levels, arms, legs, and trunk %FM increased (ES = from 0.42 to 1.29) while trunk-FFM was reduced (ES = -0.40 ± 0.26) after DTP, returning to the values observed at the end of the previous season after RTP. Legs-FFM did not change after DTP, with a substantial increase after RTP in comparison with pre-season values (ES = 0.34 ± 0.29 and 0.53 ± 0.36 for the right and left leg, respectively). Despite the small sample size of the present study, the findings indicate that elite soccer players can be allowed 2 weeks of rest during a five-week DTP, since the changes in %FM and FFM were relatively small, and FM and FFM returned to the optimal initial values for competition after the proposed RTP during the pre-season.